CULTURAL TACTICAL URBANISM FOR KIDS IN TERANG BANGSA SCHOOL AREA, SEMARANG CITY - Suwarno Kusweanto, David; Lo, Kevin; Nysa Pertiwi NS, Natania (Border: Jurnal Arsitektur, 2024)
Children are an age group that is vulnerable to becoming victims of accidents on city roads, especially with the use of roads as play spaces. Apart from that, at Terang Bangsa Elementary School, there are still outdoor spaces that are unkempt and abandoned. Previous research shows a close relationship between Tactical Urbanism and children's behavior in urban spaces. However, there has yet to be any research regarding Tactical Urbanism that formulates a design specifically intended for children. Therefore, this research aims to formulate a Tactical Urbanism design appropriate to the culture of Terang Bangsa Elementary School children. Qualitative methods were used to answer the research objectives: observation, literature review, and descriptive qualitative. Based on this method, the appropriate Tactical Urbanism design is to provide a playground that facilitates accustomed games. Tactical Urbanism suggests dividing areas into three: circulation, active, and semi-active. Each zone is equipped with furniture that can be disassembled and adapted to suit the child, and it functions as a play stimulant, relaxer, and barrier. Practical street art is needed to support children's play atmosphere. Implementing this design can change the school environment, motivate school children's activities, and become the school's identity.